The effects of COVID-19 pandemic on (new) life insurances - Olli Ropponen; Tero Kuusi; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2023)
This paper studies the life insurance demand responses to Covid-19 pandemic. It employs the unique individual-level daily data on new term life insurances together with both geographical and timely variation in the severity of the pandemic in Finland. These data are merged with the high-quality register data on the background characteristics of the customers and other Finnish population. First, we observe that the take-out of new life insurances increased by 20 % in the first half of 2020 among individuals of ages 21-60, compared to the corresponding time periods in years 2018 and 2019. The average sum insured increased at the same time by 16 %. Second, we find that the life insurance demand responds heavily to all Covid-measures, each of which may be considered as reflecting the change in the perceived death risk. We also find that the responses are larger to the country-level measures compared to the hospital district level measures. An increase in each country-level Covid-measure by 10 % implies on average an increase in the number of new life insurances by roughly 1 % (elasticity e=0.1). We also find that highly educated people and people with high life insurance deficit levels responded to Covid-pandemic more often than other people.
Keywords: G22; H31; 330; Covid-19; Life insurances; Households